Isolated Iqlab checking rules based on speech recognition system - Yousfi, Bilal; Zeki, Akram M.; Haji, Aminah (IEEE, 2017)
The act of learning and teaching of the Qur’an is the most important science for Muslim. The teacher and learner in this area they should have the provisions of tajweed rules when reading the Qur’an. There are numerous efforts made by previous systems on the development of feasible guiding techniques to the act of Tajweed. However, liking the major control variables of the practices of Tajweed in those approaches were neglected. As a way to fill this gap. This research will present a speech recognition system to recognize and identify the rules of Iqlab (Ώϼϗϻ΍). The proposed system will be capable of recognizing, identify and point out the mismatch of the iqlab rules for the verses contains the rules which made by the expert teachers stored in a database. In addition, in this research will use Mel-Frequency Cepstral Coefficient (MFCC) and Hidden Markov Models (HMM) as feature extraction and feature classification respectively.